THE CONDITIONS FOR APOPHIS 99942 APPROACHING EARTH IN 2029 - Tokovenko, A. A.; Bazey А. А. (Одеські астрономічні публікації, 2009)
The discovery of Apophis 99942 asteroid in 2004 raised a number of questions in the sphere of the asteroid threatening. On April 13, 2029, the asteroid is to pass at a close distance from Earth. The study of the path of that asteroid both before and after such close approaching showed that the repeated passing by Earth and even its collision with Earth is possible in April, 2036. In the present work, the area of the resonant return of asteroid Apophis, the Moon influence to its shape and position are considered.